Hfq-Assisted RsmA Regulation Is Central to Pseudomonas aeruginosa Biofilm Polysaccharide PEL Expression - Irie, Yasuhiko; La Mensa, Agnese; Murina, Victoriia; Hauryliuk, Vasili; Tenson, Tanel; Shingler, Victoria (Frontiers in Microbiology, 2020)
Expression of biofilm-associated genes is controlled by multiple regulatory elements, allowing bacteria to appropriately switch between sessile and motile lifestyles. In Pseudomonas aeruginosa, the post-transcriptional regulator RsmA has been implicated in the control of various genes including those related to biofilms, but much of the evidence for these links is limited to transcriptomic and phenotypic studies. RsmA binds to target mRNAs to modulate translation by affecting ribosomal access and/or mRNA stability. Here we trace a global regulatory role of RsmA to the inhibition of Vfr - a transcription factor that controls a transcriptional regulator FleQ. FleQ directly controls biofilm-associated genes that encode the PEL polysaccharide biosynthesis machinery. Furthermore, we show that RsmA cannot bind vfr mRNA alone, but requires the RNA chaperone protein Hfq. This is the first example where a RsmA protein family member is demonstrated to require another protein for RNA binding.